1999
DOI: 10.1046/j.1365-2222.1999.00569.x
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of early serial measurement of specific and total immunoglobulin E in the diagnosis of gastro‐allergic anisakiasis

Abstract: We consider a rise of total and specific IgE in the first month after an allergic reaction as a useful tool in the diagnosis of gastro-allergic anisakiasis (together with patient's history), even if the parasite cannot be seen with fibre optic gastroscopy. The important rise of total and specific IgE against A. simplex can be considered as a reaction induced by the live parasitizing larva in the context of a polyclonal immunological stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 24 publications
(26 reference statements)
4
41
0
1
Order By: Relevance
“…Infection causes a strong immune response, and a typical progression from IgM antibody to other isotypes (IgG, IgA, and IgE, etc.) has been observed during the first month of initial infection, as analyzed from serial blood sampling and immunoblotting (5,29,70,84) in which the highest antigen-specific IgE, IgG, and IgA levels are seen to occur after 1 month of infection; specific IgM shows the highest levels within 24 h and a progressive decay over the following 6 months (74). In humans, low-level worm infestations tend to be tolerated with a degree of eosinophilia, but this level of exposure does not usually induce strong T-or B-cell responses.…”
Section: Innate Immune Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Infection causes a strong immune response, and a typical progression from IgM antibody to other isotypes (IgG, IgA, and IgE, etc.) has been observed during the first month of initial infection, as analyzed from serial blood sampling and immunoblotting (5,29,70,84) in which the highest antigen-specific IgE, IgG, and IgA levels are seen to occur after 1 month of infection; specific IgM shows the highest levels within 24 h and a progressive decay over the following 6 months (74). In humans, low-level worm infestations tend to be tolerated with a degree of eosinophilia, but this level of exposure does not usually induce strong T-or B-cell responses.…”
Section: Innate Immune Responsesmentioning
confidence: 99%
“…simplex IgE levels increase rapidly during the first few days (70,72,77,85,284) and remain high for months or years (27). Hypersensitivity is usually diagnosed by skin prick tests and in vitro confirmation (specific IgE, histamine release, basophil activation test [BAT]).…”
Section: A Simplex Allergy In Humans (I) General Aspects the Potenmentioning
confidence: 99%
“…Human total IgE production in allergy kinetics plateaued at a high level for 6 mo. The tendency towards extended high levels of rat IgE indicates that the rat model can be applied to human L3 allergy (Daschner et al, 1999).…”
Section: Specific Immunoglobulin E Production and Allergy To L3mentioning
confidence: 99%
“…Human total IgE production in allergy kinetics plateaued at a high level for 6 mo. The tendency towards extended high levels of rat IgE indicates that the rat model can be applied to human L3 allergy (Daschner et al, 1999).The highest peak of the immunochemical allergic state and the biological allergic state was observed at 2 weeks and 1 week after oral reinfection in rats, respectively (Cho et al, 2006). Amano et al (1995) also observed the highest peak of the biological allergic state at 1 week post-reinfection.…”
mentioning
confidence: 94%
“…In this respect, Daschner et al [6] described the GAA as an acute allergic reaction with symptoms of hypersensitivity appearing several hours after the ingestion associated with penetration of larvae into the gastric mucosa [9] . In addition, the presence of an IgE antibody response in individuals with no apparent symptoms has been also detected 1 month after the acute GAA episode [10] . It has been suggested that a variety of effector molecules form the allergic host defence response.…”
Section: Introductionmentioning
confidence: 96%